COVID -19 Pandemic: Immediate Psycological Impact During The 3TD Stage of Lockdown among General Population of Selected Areas of Vadodara City - Ishita Shah1 , Jalpa Prajapati1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Covid -19 pandemic & lockdown has cause deliberate effect to human’s physical & mental health &trigger many psychological problems like anxiety, loneliness, stress, depression & other panic disorder.The investigators interested to find out the psychological impact of lockdown among general population &correlation with different components of modified psychosocial impact event scale. Researchers have usednon – experimental descriptive research deign with Non – randomized convenient sampling & 500samplerecruited for the study. Researchers have used standardized modified impact event scale in the form of5 point likert scale, they have identified that 366 sample(73.2%)have moderate stress,110 sample (22%)identified with severe stress & remaining 24 sample (4.8%) have mild stress. Another finding revel that eachcomponent having positive correlation with each other. The significant association of psychological impacts& selected demographic variables were found with use of modified impact event scale. Researcher haveconcluded that this type of event or diseases outbreak affect the mental health of the person , increased stressamong individual & also affect the daily life of the person.